"Language Rituals" of Hassan Wahbi: when poetic writing becomes a place of reflexivity - Harrat, Anass (Romanica Olomucensia, 2023)
Modern poetry is no longer an imaginative self-expression or a form of expression that uses metpoetry is no longer imaginative self-expression or a form of expression that uses metre and rhythm to produce poems. It now includes reflexive moments, during which the reader is invited to reinvent their vision of the poetic text. From this perspective, Hassan Wahbi wrote a poem called "Language Rituals" in 2015, in which he rejects the mimetic function of poetry and calls for fragmentary writing. For him, fragmentary writing represents a poetic form that is not only laconic but also condenses a wide poetic spectrum. In order to examine this reshaping of the poetic text as well as the embedded philosophical and aesthetic loads, a philosophical-textualist approach will be deployed. The study of such a convoluted text will lead to the following results: a) the modernity of this text is inherent in its capacity of being self-reflective; b) the poet can be described as "modern" as he reflects in and about the text; c) the questioning feature is not particular to philosophical texts but extends to contemporary poems; and d) Wahbi's text combines a metapoetic dimension along with an ethical and an existential dimension. This paper is by no means exhaustive, but it allows for a better understanding of the reflexive approach employed by Hassan Wahbi in his quest for truth.
Keywords: Hassan Wahbi; Abdelkebir Khatibi; poetry; fragmented poetry; reflexivity; poetics